The genetics of drought tolerance in conifers. Issue 4 (12th September 2017) - Moran, Emily; Lauder, Jeffrey; Musser, Cameron; Stathos, Angela; Shu, Mengjun
Summary: As temperatures warm and precipitation patterns shift as a result of climate change, interest in the identification of tree genotypes that will thrive under more arid conditions has grown. In this review, we discuss the multiple definitions of 'drought tolerance' and the biological processes involved in drought responses. We describe the three major approaches taken in the study of genetic variation in drought responses, the advantages and shortcomings of each, and what each of these approaches has revealed about the genetic basis of adaptation to drought in conifers. Finally, we discuss how a greater knowledge of the genetics of drought tolerance may aid forest management, and provide recommendations for how future studies may overcome the limitations of past approaches. In particular, we urge a more direct focus on survival, growth and the traits that directly predict them (rather than on proxies, such as water use efficiency), combining research approaches with complementary strengths and weaknesses, and the inclusion of a wider range of taxa and life stages. Contents Summary 1034 I. Introduction 1034 II. Drought tolerance 1035 III. Investigation of the genetic basis of drought tolerance: three main approaches 1037 IV. Conifer drought tolerance genetics: what we know 1038 V. Implications for the management of forests in a changing world 1042 VI. Future directions 1043 VII. Conclusion 1045 References 1045